2021
DOI: 10.5334/bc.110
|View full text |Cite
|
Sign up to set email alerts
|

Relationship-building around a policy decision-support tool for urban health

Abstract: Contemporary challenges linked to public health and climate change demand more effective decision-making and urban planning practices, in particular by taking greater account of evidence. In order to do this, trust-building relationships between scientists and urban practitioners through collaborative research programmes is required. Based on a policy-relevant research project, Complex Urban Systems for Sustainability and Health (CUSSH), this project aims to support the transformation of cities to meet environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…DSTs can play an important role in transferring information and knowledge to policy and decision makers on road safety, health services, environmental and urban health [ 145 149 ] (Additional file 13 : Appendix 13). DSTs assessed in the included studies were the CRAFT tool [ 148 ], the HENVINET DST MDB [ 150 ], the NHS Scotland DST Platform [ 148 ], the SOMNet, combined with the EbCA [ 149 ] and the European Road Safety Decision Support System [ 147 ].…”
Section: Resultsmentioning
confidence: 99%
“…DSTs can play an important role in transferring information and knowledge to policy and decision makers on road safety, health services, environmental and urban health [ 145 149 ] (Additional file 13 : Appendix 13). DSTs assessed in the included studies were the CRAFT tool [ 148 ], the HENVINET DST MDB [ 150 ], the NHS Scotland DST Platform [ 148 ], the SOMNet, combined with the EbCA [ 149 ] and the European Road Safety Decision Support System [ 147 ].…”
Section: Resultsmentioning
confidence: 99%
“…According to the OECD classification, five studies reported data from a large metropolitan area ( 28 , 31 , 37 , 38 , 41 ). Sobral, Richmond, Rennes, Bristol, Ljubljana and Sosnowiec were classified as medium-sized urban areas ( 27 , 30 , 32 , 42 ); Barcelona, San Francisco, Lisbon, Detroit and Amsterdam were classified as metropolitan areas ( 33 , 36 , 40 , 42 ); and Noarlunga, Gulfport, Hermosa Beach, Redondo Beach and Manhattan Beach as small-size urban areas ( 29 , 34 , 43 ). Matsapha and Vancouver were classified as other urban settings ( 35 , 39 ).…”
Section: Resultsmentioning
confidence: 99%
“…Multisectoral action was the strategy most frequently reported. As a lone process, multisectoral action to advance the construction of a healthy city was addressed in six (35%) studies ( 30 32 , 35 , 36 , 41 ). Five studies assessed both multisectoral action and health governance ( 27 , 29 , 33 , 38 , 39 ); three reported data on multisectoral action and civic engagement ( 34 , 37 , 40 ), and the same amount of studies assessed only civic engagement ( 28 , 42 , 43 ).…”
Section: Resultsmentioning
confidence: 99%
“…At the programme level, we apply a multi-sited ethnographic approach, which operates in diverse locations, especially in order to understand ways for strategic collaborations between researchers and participants to emerge from the fieldwork [66,67]. This is suitable for addressing the transdisciplinary, multi-agency and multi-context international nature of the programme [68]. Within this particular case study, we are using rapid ethnography.…”
Section: Methodsmentioning
confidence: 99%